The Relation Between Agility and Fundamental Offensive Skills Ending With Jump Shot And Lay Up In Youth Basketball - Sami, Fares; Mohameed, Seerzad (Journal of Physical Education, 2016)
The problem of the research lies in the bad timing of jump shot and layup due to lack of experience. The subjects were (5) youth basketball players under eighteen of the season 2015 – 2016. The results showed that agility didn’t reinforce some fundamental offensive skills ending in jump shot and layup. The researcher recommended stressing offensive fundamental skills ending jump shot and layup without connecting it with agility. The training experience of most players participating in basketball league is very little thus more time should be offered to them before getting them into the league.